PETA BARU BISNIS PERBANKAN Dl INDONESIA - Ninik Sri Rahayu (Jurnal Aplikasi Bisnis, 2017)
The Indonesian Banking Architecture isa comprehensive, basic frame work for the Indonesian banking system. In the Architecture, the policy direction for the future development of the banking industry is based on the vision of building strong and effcient banking system to create financial system stability for the promotion of national economic growth. To bring the visionof the Architecture as described above, the six pillars of the Architecture are designed to ensure the achievement of the architecture vision as follows: healthy banking structure, effective regulatory system, effective and independent supervisory system, strong banking industry, adequate infrastructure, robust customer protection.The next ten tofifteen years the banking system are expected to move the banking system towards a more optimum structure. This structure isenvisaged as follows: two or three banks likely to emerge as international banks, possessing the capacity and ability to operate on an international scale and having total capital exceeding Rp50 trillion, 3 to 5 national banks, having a broad scope of business and operating nation wide with total capital between Rp lO trillion and Rp 50 trillion, 30 to 50 banks operating as focused players, with operations focused on particular business segments according to the capability and competence of each bank. These banks will have capital of Rp lOO billion up to RplO trillion, rural banks and banks with limited scope of business, having capital of less than RplOO billion.